Proteína hidrolisada enzimatica de penas em dietas para tilápia do Nilo (Oreochromis niloticus) - Xavier, DeboraTatyane Oliveira (2022)
The fish farming activity has high levels of productivity, financial investments and income, consisting in the intensification of farming systems, demanding new technologies and alternative foods that can better provide the nutrients in the diets and meet the nutritional requirements of farmed animals. Thus, the respective studies were carried out with the objective of evaluating the inclusion of hydrolyzed feather protein (PHP) in diets for Nile tilapia on the aspects of productive, histological and enzymatic performance in different stages of cultivation. The researches were carried out with larvae and fingerlings at three different times, all with increasing levels (Control (0%), 1%, 2%, 3%, 4% and 5%) of inclusion of hydrolyzed feather protein (BRF®) in the diets and a negative control with commercial ration used in the production units. The rations were formulated to contain 38% and 34% of digestible protein, respectively, both with 3400 kcal of digestible energy/kg of diet. Recommended nutritional values for the species under study at the stage of development in which they are. In Study I, 2,520 larvae with a mean initial weight of 0.017±0.002g were randomly distributed in 21 polyethylene aquariums (120 liters of useful volume), totaling seven treatments with three replications. With a duration of 15 days of trials. Study II was an extension of experiment I. At the end of study I (15 days of experimentation), the larvae were in the fingerling stage, the weight of the experimental animals was standardized, maintaining the respective treatments and the same design, readjusting the density, with 30 fingerlings per aquarium. For this study, 630 fish with an average weight of µ = 1.67 ± 0.05 g were used, 90 fish per treatment, with 35 experimental days. For Study III, fingerlings were obtained directly from the breeding farm at the same stage of development as in Study II. For Study III, the negative control corresponding to commercial feed was eliminated, therefore, its experimental design consisted of six treatments and four replications, corresponding to 24 experimental units of 150 liters, with 30 fish per aquarium, totaling 720 animals with average weight of 1.96 ± 0.03 g. The fish were fed until apparent satiation (8:00 am, 10:00 am, 12:00 pm, 2:00 pm, 4:00 pm and 6:00 pm) with experimental diets containing different levels of hydrolysate inclusion for 30 days. The water quality parameters were measured weekly, using a multi-parameter electronic device. At the end of the experiment, the parameters of productive performance of the experimental animals were verified. The inclusion of feather protein hydrolyzate in the diets improved the zootechnical aspects of Nile tilapia larvae and fingerlings that received the test ingredient from the first days of life. Thus, it is recommended the inclusion of 2% and 1% respectively of the referred product for better productive performance in the aforementioned breeding phases. For the nursery stage in study III, no statistical differences were observed in the performance of Nile tilapia fed with PHP. Thus, the alternative ingredient proved to be potential for replacing fish meal in the diet, without compromising the parameters of productive performance of Nile tilapia fingerlings.